Revision of the Rhyacophila stigmatica Species Group in Turkey with descriptions of three new species (Trichoptera, Rhyacophilidae) - Si̇pahi̇ler Füsun (Zootaxa, 2013)
The Rhyacophila stigmatica Species Group in Turkey is revised and three new species (Rhyacophila alaplica sp. n. from northwestern Turkey, and Rhyacophila camiliensis sp. n., and R. torulensis sp. n., both from northeastern Turkey) are de-scribed and illustrated. A redescription of R. zwickorum Malicky 1972 is given. A key to the Turkish males and females of the Group is provided.